Evaluation of antifungal activity against Corynespora cassiicola by bacteria isolated from soil in the root zone of cucumber plants - LE QUOC DUY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Duy LQ. 2023. Evaluation of antifungal activity against Corynespora cassiicola by bacteria isolated from soil in the root zone of cucumber plants. Biodiversitas 24: 6584-6591. Target leaf spot caused by Corynespora cassiicola poses a major disease threat to cucumber cultivation worldwide. Reliance on chemical fungicides has raised resistance to environmental and health concerns. As cucumber production expands globally, sustainable solutions are needed. Plant Growth-Promoting Rhizobacteria (PGPR) show promise but remain underexplored against C. cassiicola in cucumber. This study aimed to assess the potency of rhizobacteria in antagonistic activity against C. cassiicola, causing cucumber target leaf spots under in vitro conditions. The present study isolated bacterial strains from cucumber soil rhizosphere and screened for antifungal activity against C. cassiicola using dual culture assays. Using quantitative assays, selected antagonistic strains were further assessed for key biocontrol traits, including ?-1,3-glucanase, chitinase, and siderophore production. Cell-free supernatants were tested for direct fungal growth inhibition using the environmental toxicity. Isolated PGPR strains showed robust C. cassiicola inhibition from 39.8% to 62.6% growth reduction. Most antagonistic isolates produced ?-1,3-glucanase, chitinase, and siderophores and suppressed pathogen growth via metabolites in their supernatants. These results demonstrate multiple biocontrol mechanisms, including enzymatic degradation of fungal cell walls, iron competition through siderophores, and antimicrobial compound secretion. Bacillus siamensis strain TV16 exhibited the strongest overall antagonism against C. cassiicola. These findings reveal the biocontrol potential of PGPR for managing cucumber-target leaf-spot disease, offering a sustainable alternative to chemical pesticides. With further optimization and field testing, PGPR-based biopesticides can be integrated into cucumber production to improve crop health while reducing fungicide reliance.